2017
DOI: 10.18632/oncotarget.18711
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 mutation impacts biological and clinical features of T-LGL leukemia

Abstract: STAT3 mutations have been described in 30-40% of T-large granular lymphocyte (T-LGL) leukemia patients, leading to STAT3 pathway activation. Considering the heterogeneity of the disease and the several immunophenotypes that LGL clone may express, the aim of this work was to evaluate whether STAT3 mutations might be associated with a distinctive LGL immunophenotype and/or might be indicative for specific clinical features.Our series of cases included a pilot cohort of 101 T-LGL leukemia patients (68 CD8+/CD4- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
78
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 32 publications
(48 reference statements)
11
78
4
Order By: Relevance
“…Somatic STAT3 mutations are preferentially located in the Src homology 2 (SH2) domain of the gene, leading to an increase of the stability of STAT3 protein dimerization that results in an enhanced transcriptional activity of pro-survival proteins (13). STAT3 mutation is preferentially found in CD8+ T-LGLL (14) and some TCRγδ LGLL cases (15), its incidence among the entire cohort of T-LGLL ranging from 11 up to 75% based on different reports (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Y640F and D661Y are the most frequent STAT3 genetic lesions, accounting for about 60% of the recognized mutations.…”
Section: Stat3 Mutationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Somatic STAT3 mutations are preferentially located in the Src homology 2 (SH2) domain of the gene, leading to an increase of the stability of STAT3 protein dimerization that results in an enhanced transcriptional activity of pro-survival proteins (13). STAT3 mutation is preferentially found in CD8+ T-LGLL (14) and some TCRγδ LGLL cases (15), its incidence among the entire cohort of T-LGLL ranging from 11 up to 75% based on different reports (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Y640F and D661Y are the most frequent STAT3 genetic lesions, accounting for about 60% of the recognized mutations.…”
Section: Stat3 Mutationsmentioning
confidence: 99%
“…The remnant other less frequent mutations include both point mutations and insertion or deletions and are mostly found in SH2 domain (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), although some missense substitutions were described in DNA-binding and coiled coil domains [(27); Figure 1]. All T-LGLL patients are characterized by STAT3 activation, that is the hallmark of every T-LGLL, but a higher amount of the phosphorylated protein has been observed in cases with STAT3 mutations (13,14,17). Functional studies revealed that even if in different locations, most of the reported mutations lead to a higher protein transcriptional activity and cytokine responsiveness (13,27).…”
Section: Stat3 Mutationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence on the genomic landscape of T-LGLL pointed to a key role of somatic mutations within JAK/STAT (mostly in STAT3 and STAT5B genes) and Ras/MAPK pathways [3][4][5][6][7][8][9][10] . In ANKL and NKTCL, JAK2 and STAT3 mutations, lesions of epigenetic modifiers and tumor suppressors were detected [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%